Genetic Diversity of Sweet Potato (Ipomoea Batatas (L.) Lam) Accessions from Nigeria and Niger Based on Agro-Morphological - Abed, Josefina Ndamononghenda; Oselebe, Happiness Ogba; Chukwu, Samuel Chibuike; Mourtala, Issa Zakari Mahaman (International Journal of Environment, Agriculture and Biotechnology, 2024)
Utmost tropical nations regard the sweet potato( Ipomoea batatas(L.) Lam.) as their most significant chief crop. It's substantially privileged for its capability to deter disaster, improvement, and produce with many inputs. A study was carried out during the 2020 and 2021 growing time seasons in a field trial conducted at the University of Ebonyi State – CAS , to determine variability among sweet potato accessions, and identify traits that are positively and significantly associated with yield and accessions with high yield. A randomized complete block design with three replications was used to determine variability among sweet potato accessions, The results of both years combined statistical analysis indicated that the types significantly varied in terms of all yield and yield- related traits. As a result, the Umu SPO 3 acquired had the topmost values of average root storage in both the 2020 (5.2 cm) and 2021 (2.4 cm) growing seasons. In both 2020 and 2021 growing seasons and over time combined analysis, the haughtiest average root yield (2.67 Kg), and total root yield(8.89 t/ ha) were recorded for Koudakou. PCV was advanced than GCV suggesting a major environmental influence on those characters. Low heritability coupled with high, moderate, and low inheritable advance in percent of mean was observed in all characters. Traits considered in the study revealed positive and significant correlations. The grouping of accessions into two main clusters highlights genetic relationships among them. Understanding these relationships can help breeders identify potential parent lines for cross-breeding, which can lead to the development of new varieties with desirable traits.